A vow so bold and deadly ebook - Kemmerer, Brigid (Cursebreakers, 2021)
Kingdoms will clash. Choose your side. The incredible conclusion to New York Times bestselling author Brigid Kemmerer's Cursebreaker series. Face your fears, fight the battle. Emberfall is crumbling fast, torn between those who believe Rhen is the rightful prince and those who are eager to begin a new era under Grey, the true heir. Grey has agreed to wait two months before attacking Emberfall, and in that time, Rhen has turned away from everyone—even Harper, as she desperately tries to help him find a path to peace. Fight the battle, save the kingdom. Meanwhile, Lia Mara struggles to rule Syhl Shallow with a gentler hand than her mother. But after enjoying decades of peace once magic was driven out of their lands, some of her subjects are angry Lia Mara has an enchanted prince and a magical scraver by her side. As Grey's deadline draws nearer, Lia Mara questions if she can be the queen her country needs. As the two kingdoms come closer to conflict, loyalties are tested, love is threatened, and an old enemy resurfaces who could destroy them all, in this stunning conclusion to bestselling author Brigid Kemmerer's Cursebreaker series.